2010
DOI: 10.1080/08838151003734995
|View full text |Cite
|
Sign up to set email alerts
|

I Am What I Watch: Voyeurism, Sensation Seeking, and Television Viewing Patterns

Abstract: This article investigates the role of viewers' personality traits, sensation-seeking, and voyeurism in relation to reported consumption of voyeuristic program content in various television genres. A uses and gratifications approach was employed to identify factors predicting appeal of particular TV programs. The study combines two types of media research: survey and content analysis. Results were combined to create the Voyeurism Television Consumption Index (VTCI) for each genre of TV programming. Both sensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
19
0
2
Order By: Relevance
“…That TV viewing may have a stronger impact on high-sensation (vs. low-sensation) seekers' estimates of smoking prevalence and perceptions about smokers is also evidenced by a growing body of literature on the relationship between sensation seeking and media choice (e.g., Bagdasarov et al, 2010). For example, sensation seeking has been found to predict exposure to action-oriented and violent media (e.g., Hoffner & Levine, 2007).…”
Section: The Moderating Role Of Sensation Seekingmentioning
confidence: 92%
“…That TV viewing may have a stronger impact on high-sensation (vs. low-sensation) seekers' estimates of smoking prevalence and perceptions about smokers is also evidenced by a growing body of literature on the relationship between sensation seeking and media choice (e.g., Bagdasarov et al, 2010). For example, sensation seeking has been found to predict exposure to action-oriented and violent media (e.g., Hoffner & Levine, 2007).…”
Section: The Moderating Role Of Sensation Seekingmentioning
confidence: 92%
“…Among the studies that have considered uses and gratifications using psychological traits, often the predictors are specific to the study and not drawn from a general psychological index. Examples of this can be seen in Bagdasarov et al's (2010) examination of the specific traits of sensation seeking and voyeurism in the uses and gratifications framework.…”
Section: Uses and Gratificationsmentioning
confidence: 97%
“…In a similar vein, research has identified the genre as an interesting field to examine various phenomena. A few scholars even concentrated on the reasons why viewers engage in the reception of reality TV shows (e.g., Papacharissi & Mendelson, 2007;Bagdasarov et al, 2010;Baruh, 2010). Some studies dealt with different features of the genre (e.g., Kilborn, 1994;Nabi et al, 2003;Hill et al, 2007), its authenticity (e.g., Rose & Wood, 2005;Allen & Mendick, 2013) or viewers' consumption patterns (e.g., Lundy et al, 2008) and controversies surrounding reality TV (e.g., Biltereyst, 2004).…”
Section: Relevance Of Reality Tv For Researchmentioning
confidence: 99%